Morphological characteristics, muscle strength, and anaerobic power performance of wheelchair basketball players - Sandra Aires Ferreira; William Cordeiro de Souza; Matheus Amarante do Nascimento; Marcus Peikriszwili Tartaruga; Bruno Sergio Portela; Luis Paulo Gomes Mascarenhas; Marcos Roberto Queiroga (Universidade Federal de Santa Catarina, 2017)
The aim of this study was to provide a descriptive analysis of the morphological structure, muscle strength, and anaerobic power performance of the upper limbs of wheelchair basketball athletes. Eleven male players (33.2 ± 10.6 years, 71.8 ± 15.8 kg) were submitted to anthropometric measurements and dynamometry (kg), medicine ball throwing (m) and wingate arm tests (W). he results showed sitting height (79.7 ± 4.6 cm), relative body fat (20.7 ± 7.6%), handgrip strength and explosive muscle strength (50.1 ± 10.6 kg and 3.9 ± 1.1 m, respectively), as well as peak power (316.8 ± 126.2 W), mean power (160.5 ± 76.5 W) and fatigue index (50.4%) lower than the performance of other wheelchair basketball athletes. he morphological characteristics and performance of athletes in the present study suggest disadvantages when compared to other wheelchair basketball athletes.